Modified experimental method to investigate micro transport in the shale matrix for shale gas production - Hu, Zantong; Deng, Yonghong; Li, Jingxuan; Wu, Xiaojun; Bai, Jinmei; Tian, Junqiang (Frontiers in Energy Research, 2023)
Matrix permeability is the primary transport property for shale gas recovery, due to the special production process of gas from matrix to wellbore. With the micro pore size of shale matrix, it is necessary to consider micro transport mechanisms for the obtained permeability from macro experimental techniques. In this study, the macro experimental permeability was investigated in micro way, by the analyzation of pressure drop curves of shale matrix at high- and low-pressure experimental conditions, with modified numerical model containing micro transport mechanisms. As selected parameters, porosity, pore radius and tortuosity were regressed to obtain apparent permeabilities of three samples. The analysis shows that, tortuosity is much higher than macro one, and has been proved to be necessary and reasonable. The Knudsen diffusion and slippage effect control the micro transport of shale matrix at low and high pressure, separately, which is the main difference of macro and micro transports. Slippage flow weight factor helps to increase of slippage flow proportion with pressure. Higher pore radius and tortuosity both could weaken the effect of Knudsen diffusion, and slippage flow appears positive relationship with pore size at high pressure. This research provides an inspiration to shale transport study and a micro perspective theoretical guidance for the macro recovery of in-site shale gas reservoir.